MEMBANGUN PENGETAHUAN ANAK USIA DINI MELALUI PERMAINAN KONSTRUKTIF BERDASARKAN PERSPEKTIF TEORI PIAGET - Ginting, Meta Br (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2018)
AbstractKnowledge is important in the child development process because knowledge is the basis of attitudes and self skills formation . Familiarizing children to build their own knowledge early can make them capable for finding ideas to solve problems, having good self-confidence and initiative. Children are active beings who can build their own knowledge through play. When playing, child exploring, finding and utilizing the objects around them to be meaningful. Exploring objects enable the assimilation and accommodation process occur in forming new schemes. Constructive play is one of the game that is exploring objects. By constructive play it is possible for the child to acquire knowledge through assimilation and accommodation process, so the game can help the child form a new scheme based on the experience as well as generate knowledge.Keywords: Knowledge, Constructive Play, Piaget Theory